The Analysis of Slang Words in Romantic Comedy Movie - Kadek Ayu Teja Murthi; I Made Suastra; Ni Luh Putu Krisnawati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The title of this study is The Analysis of Slang Words in Romantic Comedy Movie entitled 500 Days of Summer. This study aims at categorizing the types and functions of slang used by the characters in the 500 Days of Summer. In this study, the method of collecting data were the documentation and observation method, then the data were analyzed using the content analysis method using the theory proposed by Allan and Burridge (2006). According to Allan and Burridge (2006), there are five types of slang namely fresh and creative, flippant, imitative, acronym, and clipping. Furthermore, there are seven functions of slang namely to address, to initiate relax conversation, to humiliate, to form intimate atmosphere, to express impression, to reveal anger, and to show intimacy. The result of this study reveals that all the types of slang proposed by Allan and Burridge (2006) were used by the characters in the movie entitled 500 Days of Summer. Moreover, six out of seven functions of slang proposed by Allan and Burridge (2006) were employed by the characters in the 500 Days of Summer movie script, only to form intimate atmosphere did not employ by the characters in the movie script.